2019
DOI: 10.1093/jas/skz258.936
|View full text |Cite
|
Sign up to set email alerts
|

PSXIII-8 Acute challenge with a DON-contaminated diet induce transient changes on microbiota composition in finishing pigs

Abstract: The present study aimed at describing the impact of a deoxynivalenol (DON) - contaminated diet on microbiota composition. A total of 147 (Large White x Landrace) x Piétrain pigs from two replicates were affected to four different experimental treatments. Pigs in the control group (CC) received a control diet from 99 to 154 days of age. Groups DC, CD, and DD were given the DON-contaminated diet (3.02 mg DON/kg feed) for 7 days at 113, at 134, and at 113 and 134 days of age, respectively. The DON-contaminated di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In this study, the DON exposure impacted the ADFI, ADG, and FCR of the pigs at 119 and 140 days of age as previously detailed by Serviento et al [27], but no impact on the performances was observed after the two-week recovery at 154 days of age. In addition, a transient impact on the microbiota composition has been observed [28]. However, in our experimental conditions, DON exposure did not impact the enterotype repartition among the animals nor their possible instability, suggesting that the enterotypes are insensitive to DON exposure.…”
Section: Discussionmentioning
confidence: 46%
“…In this study, the DON exposure impacted the ADFI, ADG, and FCR of the pigs at 119 and 140 days of age as previously detailed by Serviento et al [27], but no impact on the performances was observed after the two-week recovery at 154 days of age. In addition, a transient impact on the microbiota composition has been observed [28]. However, in our experimental conditions, DON exposure did not impact the enterotype repartition among the animals nor their possible instability, suggesting that the enterotypes are insensitive to DON exposure.…”
Section: Discussionmentioning
confidence: 46%